Avaliação da eficácia do fitoterápico a base de Cymbopogon citratus no tratamento da Candidose em usuários de prótese - Barroso, Keila Martha Amorim (2009)
Objective: To evaluate the effectiveness of the gel Cymbopogon citratus (DC.) Stapf (lemon grass) in the treatment of oral candidiasis in patients weares of prosthesis, comparing the results with Daktarin® oral gel. To this end, we carried out a randomized, blinded, controlled. Methods: The sample consisted of 30 adult patients, volunteers of both sexes, who underwent clinical examination and laboratory tests (mycological) for diagnosis of oral candidiasis. Patients were randomly assigned to experimental group consisted of 20 patients who used the gel Cymbopogon citratus and control group comprised 10 patients who used Daktarin® oral gel. Both requirements were recommended for use three times daily for a period of 15 days. Clinical and mycological analysis of the oral mucosa were performed on day 1 before the start of treatment in the 8th and the 16th day after initiation of medication. Analysis was performed using descriptive statistics and applied chisquare and Kruskal-Wallis test, considering significant p <0.05. Results: In the experimental group after 15 days of treatment, 80% of patients were cured in the control group and the healing occurred in 90% of patients. Candida albicans was the most prevalent (76.6%). Conclusions: According to the results obtained in clinical research concluded that the gel base of the essential oil from leaves of Cymbopogon citratus was effective in the treatment of oral candidiasis in prosthesis users. The results are promising and indicate this as an alternative herbal treatment for oral candidiasis.